Pengaruh Promosi, Kualitas Pelayanan dan Harga Terhadap Keputusan Pembelian Mobil Daihatsu (Studi Pada Dealer Asco Daihatsu Cabang Pasar Minggu) - Billy Chandra Febriansyah (CV. Syntax Corporation Indonesia, 2021)
The automotive world is growing along with the increase in population. Industry 4.0 directly affects technology in today's cars and will continue to develop according to the times. Daihatsu is a well-known car company with the most sales holders in Indonesia and this study aims to determine the effect of promotion, service quality and price on the decision to purchase a Dahatsu car at the Asco Daihatsu dealer, Pasar Minggu branch. The number of respondents involved in this study were 100 respondents. The sampling technique used was non-probability sampling with purposive sampling method and practice in the field using accidental sampling. Collecting data using a questionnaire with a Likert measurement scale. The respondents are all consumers who have bought a car at the Asco Daihatsu dealer in the Pasar Minggu branch. The research data were analyzed using Microsoft Excel 2010 and the Statistical Package For the Social Science (SPSS) Version 25 for Windows. Based on the results of the analysis in this study, it was found that: (1) Promotion had an effect on purchasing decisions; (2) Service quality has an effect on purchasing decisions; (3) Price has an effect on purchasing decisions. Overall, the results of the analysis in this study indicate that promotion, service quality and price simultaneously affect purchasing decisions.